The money we'll save - Cole, Brock (Farrar Straus Giroux, 2011)
In nineteenth-century New York City, when Pa brings home a young turkey in hopes of saving money on their Christmas dinner, his family faces all sorts of trouble--and expense--in their tiny apartment.